A Survival Analysis of Gastric or Colorectal Cancer Patients Treated With Surgery: Comparison of Capital and a Non-capital City - Hong, Nam-Soo; Lee, Kyeong Soo; Kam, Sin; Choi, Gyu Seog; Kwon, Oh Kyoung; Ryu, Dong Hee; Kim, Sang Won (Journal of preventive medicine and public health, 2017)
The objective of the present study was to compare prognosis of patients with gastric or colorectal cancer according to places where they received surgeries. The cancer patients underwent surgeries in sampled hospitals located in Daegu were matched 1:1 to the patients who visited sampled hospitals in Seoul using propensity score method. After the occurrences of death were examined, Kaplan-Meier method was used for survival analysis and the log-rank test was performed to compare the survival curves. A total of six out of 291 gastric cancer patients who had surgeries in Daegu died (2.1%) and ten deaths (3.4%) occurred from patients went Seoul hospitals. Out of 84 gastric cancer patients who had chemotherapy after surgeries in Daegu, 13 (15.5%) patients died while 18 (21.4%) deaths occurred among patients underwent surgeries in Seoul. Six deaths (6.9%) out of 87 colorectal cancer patients who had surgeries in Daegu were reported. Five patients (5.7%) died among the patients underwent surgeries in Seoul. Among the colorectal cancer patients with chemotherapy after surgeries, 13 patients (12.4%) who visited hospitals in Daegu and 14 (13.3%) patients who used medical centers in Seoul died. There were no significant differences according to places where patients used medical services. The result of this study is expected to be used as basic data for policy making to resolve centralization problem of cancer patients and to help patients to make rational choices in selection of medical centers.